Class I and Class II Lanthipeptides Produced by Bacillus spp. - Barbosa, Joana
The increasing number of multidrug-resistant pathogens, along with the small number of new antimicrobials under development, leads to an increased need for novel alternatives. Class I and class II lanthipeptides (also known as lantibiotics) have been considered promising alternatives to classical antibiotics. In addition to their relevant medical applications, they are used as probiotics, prophylactics, preservatives, and additives in cosmetics and personal-care products. The genus Bacillus is a prolific source of bioactive compounds including ribosomally and nonribosomally synthesized antibacterial peptides. Accordingly, there is significant interest in the biotechnological potential of members of the genus Bacillus as producers of antimicrobial lanthipeptides. The present review focuses on aspects of the biosynthesis, gene cluster organization, structure, antibacterial spectrum, and bioengineering approaches of lanthipeptides produced by Bacillus strains. Their efficacy and potency against some clinically relevant strains, including MRSA and VRE, are also discussed. Although no lanthipeptides are currently in clinical use, the information herein highlights the potential of these compounds.